1998
DOI: 10.1080/10916469808949788
|View full text |Cite
|
Sign up to set email alerts
|

The Solubility and Three-Dimensional Structure of Asphaltenes

Abstract: The tendency of the asphaltenes to form aggregates in hydrocarbon solution is one of their most characteristic features and has tended to complicate the determination of the structure of petroleum. In addition, if the composition and properties of the precipitated asphaltenes reflect those of the micelles in solution, the latter should be considered as mixed micelles. This is a reasonable assumption in view of the large quantities of soluble resins found in the precipitated solid.Empirical observations indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…Resin molecules are smaller and lower in molecular weight compared to asphaltene molecules, so the asphaltene micelles are expected to be surrounded by more than one resin molecule [91,92]. Indeed, the quantitative ratio of Asphaltenes Resins Aromatics Saturates Fig.…”
Section: Interaction Of Resin and Asphaltenementioning
confidence: 97%
“…Resin molecules are smaller and lower in molecular weight compared to asphaltene molecules, so the asphaltene micelles are expected to be surrounded by more than one resin molecule [91,92]. Indeed, the quantitative ratio of Asphaltenes Resins Aromatics Saturates Fig.…”
Section: Interaction Of Resin and Asphaltenementioning
confidence: 97%
“…Previous work has suggested that asphaltenes can adsorb and even occlude compounds, including hydrocarbons, within their complex three-dimensional structures (Schabron and Speight, 1998). Well protected from secondary alteration events, these occluded hydrocarbons represent the original oil derived from kerogen (Liao et al, 2006).…”
Section: Release Of the Hydrocarbons Adsorbed/occluded Inside Asphaltmentioning
confidence: 99%
“…An important corollary of petroleum composition is that the mole fraction of resins is always larger that that of asphaltenes and hence the micelles are expected to be richer in resins (Schabron and Speight, 1998). The micelle center would be formed from polar asphaltene molecules that would be surrounded by one or more of the resin molecules that are placed between the center and the periphery thereby masking the polar functions.…”
Section: Resin-asphaltene Interactionsmentioning
confidence: 99%